Cytokines, Adipokines, and Bone Markers at Rest and in Response to Plyometric Exercise in Obese vs Normal Weight Adolescent Females - Kurgan, Nigel; McKee, Katherine; Calleja, Melissa; Josse, Andrea R.; Klentrou, Panagiota (Frontiers in Endocrinology, 2020)
Background: In adults, excess adiposity has been associated with low-grade, chronic inflammation and compromised bone health, but less is known about these linkages in children. The purpose of this study was to compare the circulating levels of inflammatory cytokines, adipokines, osteokines and bone markers at rest and in response to plyometric exercise between obese and normal weight adolescent females. Methods: Ten normal weight (BMI=21.3±2) and ten obese (BMI=32.9±4), postmenarcheal females, aged 13-17 years, performed one bout of plyometric exercise (5 circuits; 120 jumps). Blood samples were taken at rest, 5 min, 1h and 24h post-exercise. Tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), insulin, leptin, osteocalcin, carboxy-terminal telopeptide (CTX), sclerostin and parathyroid hormone (PTH) were measured in serum. Results: Cytokines were not different between groups at rest or over time with IL-6 increasing (+31%; p=0.04) 5 min post-exercise and TNF-α decreasing (-9%; p=0.001) 1h post-exercise. Insulin and leptin were higher in the obese compared to normal weight females. In both groups, insulin significantly increased 5 min post-exercise but remained elevated 1h post-exercise only in the obese group. Leptin did not change in response to exercise. Osteocalcin was lower in the obese group across time and increased (+12%; p=0.02) 24h post-exercise in both groups. CTX was similar between groups at rest and decreased (-24%; p<0.001) 1h post-exercise. Sclerostin was similar between groups at rest, but there was a significant interaction reflecting an increase (+29%; p=0.04) 5 min post-exercise in the obese group and a non-significant decrease (-13%; p=0.08) in the controls. PTH increased 5 min post-exercise, dropped 1h post-exercise to lower than pre-exercise, and returned to baseline 24h post-exercise in both groups. Conclusion: Obese adolescent females from our study had no evidence of resting inflammation or differences in bone resorption but show blunted bone formation when compared to normal weight controls. The direction and temporal changes in inflammatory cytokines, adipokines and bone turnover markers to exercise were similar in both groups, reflecting an overall bone anabolic response for most biomarkers, except sclerostin, which increased only in the obese females immediately post-exercise, suggesting a different systemic regulation of sclerostin depending on adiposity.